Hard hat detection in video sequences based on face features, motion and color information - Shan Du; Shehata, M; Badawy, W (2011 3rd International Conference on Computer Research and Development, 2011)
Human's safety in construction areas is vital. A hard hat is required to enter a construction area. Stopping a person who is not wearing a hard hat entering a construction area is very important. Video-based surveillance to detect hard hat is a new solution to this safety problem. This paper brings different video processing techniques together to construct a framework for fast and robust hard hat detection in construction areas. The proposed system can detect face and hard hat in real time.